2011
DOI: 10.1002/aenm.201100128
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterization of a Low‐Bandgap Crystalline Polymer:PCBM Bulk Heterojunction Solar Cells

Abstract: ]phenyl-C61-butyric acid methyl ester (PCBM) were investigated under different processing conditions. The surface morphologies and vertical segregation of the "As-Spun", "Pre-Annealed", and "Post-Annealed" fi lms were studied by scanning force microscopy, contact angle measurements, X-ray photoelectron spectroscopy, near-edge X-ray absorption fi ne structure spectroscopy, dynamic secondary ion mass spectrometry, and neutron refl ectivity. The results showed that PSBTBT was enriched at the cathode interface in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 45 publications
6
69
2
2
Order By: Relevance
“…For P3HT:PCBM BHJ OPVs the optimal blend ratio is 1:0.8, which corresponds to an optimal polymer fraction of 0.56 [27,28]. By contrast, the optimal composition reported for PSBTBT:PCBM BHJ OPVs is 1:1.5 and corresponds to an optimal polymer fraction of 0.40 [23]. Previous studies have shown that the device performance decreases significantly the farther the polymer fraction is from its optimal value [29,30].…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…For P3HT:PCBM BHJ OPVs the optimal blend ratio is 1:0.8, which corresponds to an optimal polymer fraction of 0.56 [27,28]. By contrast, the optimal composition reported for PSBTBT:PCBM BHJ OPVs is 1:1.5 and corresponds to an optimal polymer fraction of 0.40 [23]. Previous studies have shown that the device performance decreases significantly the farther the polymer fraction is from its optimal value [29,30].…”
Section: Resultsmentioning
confidence: 79%
“…Static water contact angles for P3HT (106 7 0.3°) [24], PSBTBT (104.3°) [23] and PCBM (50.6°) [23] have been reported. While contact angles for conducting polymers are highly dependent upon the level of doping of the polymer sample, these values indicate that the surface energy of PSBTBT is similar to that of P3HT.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Russell et al used a broad range of techniques to investigate the morphology of the PSBTBT/PCBM blends and the evolution of the morphology by thermal annealing. 101 The results showed that PSBTBT was enriched at the cathode interface in the films immediately after spin coating and thermally annealing the films led to an increase in the concentration of PSBTBT at the surface. However, if an electrode was evaporated onto the surface of the film initially, thermal annealing was found to increase the concentration of PCBM at the electrode (cathode) interface [ Fig.…”
Section: Polyfluorene-based Polymermentioning
confidence: 81%
“…However, unlike their ''hard'' semiconductor analogs, the ''soft'' nature of organic semiconductors-referring specifically to the response of the nuclear framework upon exciton generation-conspires to significantly limit charge mobility in these materials, and hence overall device efficiency. 9, 10 An issue of perhaps equal importance is the limitation on mobility imposed by morphological heterogeneities in polymerblend thin films, which has prompted a great deal of recent research aimed at controlled morphologies for long-range transport of charges. [11][12][13][14] In this mini-review, we discuss recent reports in the literature highlighting the connection between polymer architecture, morphology and supramolecular structure, and the fundamental photophysical processes behind charge generation and separation.…”
Section: Introductionmentioning
confidence: 99%